Conjectural History and Scottish Philosophers - Emerson, Roger (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1984)
Abstract"Conjectural history" is used here to "denote any rational or naturalistic account of the origins and development of institutions, beliefs or practices not based on documents or copies of documents or other artifacts contemporary (or thought to be contemporary) with the subjects studied." Many recent historians have focused on the apparent emergence within Scotland of a large number of sophisticated conjectural histories around ¡750, and analysed them within the framework of a Marxist-oriented social science. This paper argues that such a perspective is "inappropriate and misguided." If one looks at these works as an outcome of what went before, rather than a forerunner of what came after, they begin to lose their modernistic flavour.Conjectural histories of the Scottish Enlightenment were based essentially on four sources: the Bible and its commentaries, the classics, modern works of philosophy and travel accounts. Each had an influence on the works produced. The parallels between the Biblical and the secular conjectural histories are, for example, instructive and it is clear that no Scottish historian could consistently hold a doctrine of economic deter- minism or historical materialism and still reconcile this position with his Calvinist beliefs. Works such as Lucretius' On the Nature of Things had influenced the con- jectural histories of the Renaissance and continued to be used by the Scots just as they were by the English deists, whose speculations about historical development were also helpful to Scottish writers. Travel accounts provided information concerning mankind at various stages of civilization, but no explanation of the developmental process.While the study of history was a popular pursuit during the Scottish Enlightenment this inte rest followed trends on the continent and elsewhere. Furthermore, an examination of the great works of this period suggests that they were firmly based on the writings of scholars of a generation before. Certainly the leading writers of the "golden age" from roughly 1730 to 1790 gave a more sophisticated, detailed and elaborate treatment cf these ideas, but the sources, problems and concepts which they elucidated were not new. In their analyses, they did not employ historical materialism or economic determinism, though they were undoubtedly more political-economic, dynamic and secular in their attitude. They desired change for Scotland out of a patriotic regard for the comparative backwardness of their country, but the causes and cures for that condition were not fundamentally economic in nature. If these writings are examinedas a unit, and seen in context, the conjectural historians of the Scottish Enlightenment appear to be an understandable outcome of their intellectual milieu. The author supports this conclusion by a close examination of the work of Hume and Smith. This further explicates his theme that a nascent economic determinism was not the impetus for this writing that recent historians have read into these works.